The reproductive biology of island plants: the Juan Fernández and Canary Islands (Facilitated by the work of Arnoldo Santos Guerra) - Anderson, G. J. (2013)
Knowledge of reproductive biology is fundamental to understanding successful colonization and subsequent evolution of island plants, to founding effective conservation programs for island biota, and for the insights provided from island studies to understanding the evolution of plants in general. We focus on the reproductive biology of plants of the Canary Islands via a comparison with that of plants from the Chilean Juan Fernández (Robinson Crusoe Islands). We focus on breeding systems (i.e., compatibility, ability to self pollinate) and pollination. The breeding system of the progenitors of island lineages are inferred to assess the usual interpretation: i.e., that successful colonists are self compatible, i.e., following ‘Baker’s Law’ vs. the alternative of a mixed breeding system (‘leaky’ self incompatibility). We briefly review the mechanisms promoting outcrossing in self compatible hermaphroditic species. We assess whether current floral forms reflect pollination features of the colonizing ancestors or whether they represent selection on islands in situ. . The limited range of pollinators available to new island colonists especially of younger archipelagoes, forces adaptation to new syndromes that are not always reflected in their floral morphology or nectar. Despite the broad interest in island plants, there are few comprehensive studies of either breeding systems or pollination biology. Thus, generalizations about island systems can lead to misunderstandings: as Baker exhorted nearly a half century ago, more studies of island plant reproductive biology are needed. Furthermore, conservation programs will not be effective without a knowledge of reproductive biology of island natives.